Strategi Pemerintah Simeulue dalam Penanganan Prevalensi Stunting pada Anak Balita - Miri Susanti; Nellis Mardhiah (Journal of Social and Policy Issues, 2022)
Stunting is a condition of failure to thrive in toddlers, the government continues to campaign about the dangers of stunting, and stunting in Simeulue district is the 2nd highest in Aceh, so it is very necessary to handle this case. Based on the Simeulue Regent's Regulation Number 13 of 2019 concerning Integrated Stunting Prevention and Handling in the Village, it is based on the election of Simeulue Regency as the national stunting locus set by the Central Ministry. The determination was ratified through the decision of the head of the Netional Development Planning Agency of the Republic of Indonesia number 42 of 2020. The cause of the high stunting rate in Simeulue is the lack of nutrition in children under five, which stems form the lack of funds and posyandu facilities such as measuring instruments and weighing equi [ment (dacing) which are not fully available at every posyandu.  The purpose of this study is to describe the Government's strategy in overcoming the prevalence of stunting in children under five in Simeulue Regency and how the government’s efforts in builing cooperation with the perties hendling stunting prevention in children under vive in Simeulue Regency. Using qualitative methods and data obtained from interviews with Mr. Andre as the head of the social welfare sub-sector and then analyzed. The results of the research, the government carried out eight stunting convergence actions and each action has its own implementation instrument and givernment also involves stakeholders to reach out.